Prognostic significance of tumor-infiltrating lymphocytes in predicting outcome of distal cholangiocarcinoma in Thailand - Intarawichian, Piyapharom; Sangpaibool, Sirada; Prajumwongs, Piya; Sa-Ngiamwibool, Prakasit; Sangkhamanon, Sakkarn; Kunprom, Waritta; Thanee, Malinee; Loilome, Watcharin; Khuntikeo, Narong; Titapun, Attapol; Jareanrat, Apiwat; Thanasukarn, Vasin; et al. (Frontiers in Oncology, 2022)
Distal cholangiocarcinoma (dCCA) patients generally have poor outcomes because of late presentation and diagnosis. Therefore, prognostic factors for predicting outcomes are essential to improve therapeutic strategies and quality of life. Tumor-infiltrating lymphocytes (TILs) have been reported as a prognostic predictor in several cancers. However, their role in dCCA is still unclear. This study aimed to evaluate the association of TILs with outcome in dCCA patients. 52 patients were evaluated for the percentage of TILs in their cancers and a median TILs level was used to divide the patients into two groups. Survival, multivariate and correlation analysis were performed to determine prognostic factors. Results showed that a low TILs level was associated with poor survival. Multivariate analysis revealed TILs as an independent factor for poor outcome. Moreover, TILs were markedly correlated with growth patterns, and both were applied to classify dCCA patients. Subgroups of TILs with growth pattern incorporation improved stratification performance in separating good from poor patient outcomes. This study suggested that TILs could be a prognostic factor for predicting survival and for clustering dCCA patients to improve prognostication capability. This finding may be incorporated into a new staging system for stratifying dCCA in Thailand.